1999
DOI: 10.1007/s001340050786
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin inhibits heat shock protein 70 (HSP70) expression in peripheral blood mononuclear cells of patients with severe sepsis

Abstract: Endotoxin inhibits HSP70 expression in PBMC ex vivo. In vivo, the suppression of HSP70 expression induced by endotoxin and high levels of proinflammatory cytokines may contribute to the cellular dysfunction of immunocompetent cells concerning antigen presentation, phagocytosis and antibody production associated with decreased resistance to infectious insults during severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 24 publications
1
13
0
2
Order By: Relevance
“…We also demonstrated that SA induced the expression of newly synthesized HSP70. Since there are a number of reports on the protective role of HSP70 in LPS-induced tissue injury (9,17,22,28), it was suggested that the prevention of LPS-induced injury by SA might be related to SA-induced heat shock response.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that SA induced the expression of newly synthesized HSP70. Since there are a number of reports on the protective role of HSP70 in LPS-induced tissue injury (9,17,22,28), it was suggested that the prevention of LPS-induced injury by SA might be related to SA-induced heat shock response.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that HSP70 influences the cytokine milieu release, mediating an optimal inflammatory response dependent on the level of stress [21], an effect supported by others [50,51].…”
Section: Discussionmentioning
confidence: 69%
“…It is likely that this GLN deficiency leads to a condition in which the patient is unable to induce HSP expression appropriately. Preliminary studies in immune cells taken from critically ill patients support this conclusion [14,15]. This would place the critically ill individual in a compromised position in which appropriate tissue protection, immune regulation, and preservation of metabolic function could be significantly impaired.…”
Section: Resultsmentioning
confidence: 75%
“…In this study, adenoviral transfection of HSP-70 into pulmonary epithelium ameliorated the occurrence of ARDS following sepsis. Clinical data reveal that the expression of HSP-70 is impaired in lymphocytes of patients with severe sepsis [14,15].…”
Section: Introductionmentioning
confidence: 99%